Inhibition of Neutrophil Function by Barleria Lupulina lindl and Clinacanthus nutans (burm. F.) Lindau - Wanikia, Payong; Sujayanont, Pacharawan; Yoosook, Chalobon; Reutrakul, Vichai (Journal of Basic and Applied Pharmacology, 2015)
Barleria lupulina Lindl and Clinacanthus nutans (Burm. f.) Lindau, both belonging to the family Acantaceae, have been widely used in Thai folkore medicine as an anti-inflammatory agents and for the treatment of insect bite, allergic response and herpes infection. However, the mechanisms underlying their activities in these treatments have never been reported. In the present study, extracts from the leaves and twigs of B. lupulina and C. nutans were investigated for their inhibitory activities on neutrophil functions, including neutrophil chemotaxis, superoxide anion generation (SAG) and degranulation. It was found that B. lupulina (10-1000 μg/ml) and C. nutans (10-1000 μg/ml) inhibited fMLP-induced neutrophil chemotaxis in a concentration-dependent manner with IC50 = 8.0 ± 2.2 μg/ml and IC50 = 11.9 ± 2.2 μg/ml, respectively. Both B. lupulina and C. nutans (10-1000 μg/ml) caused a concentration-related inhibition of fMLP-induced SAG with IC50 for B. lupulina was 42.4 ± 10.7 μg/ml and for C. nutans 62.2 ± 9.2 μg/ml. These concentrations of both herbs also inhibited fMLP-induced elastase release in a concentration-dendent manner with IC50 = 145.7 ± 15.1 μg/ml and IC50 = 86.1 ± 18.5 μg/ml, respectively. The results also showed the inhibitory effects of B. lupulina (10-1000 μg/ml) and C. nutans (10- 1000 μg/ml) on neutrophil MPO production, giving IC50 = 64.1 ± 10.2 μg/ml and IC50 = 48.2 ± 11.1 μg/ml, respectively. These findings suggest that inhibition of neutrophil activation by these herbs may be attributed, in part, to their anti-inflammatory activities.